2010
DOI: 10.1086/653837
|View full text |Cite
|
Sign up to set email alerts
|

Engaged Anthropology: Diversity and Dilemmas

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(172 citation statements)
references
References 65 publications
0
153
0
14
Order By: Relevance
“…In our review of journal articles, we observed that anthropology articles mentioned "colonialism" nearly 16 times as often as management journals and "racism" nearly 5 times as often. We are not surprised, given the selfconsciousness of the discipline about its ambivalent historical connection with colonial administrations (Baba, 2009;Comaroff, 2010;Low & Merry, 2010). Moreover, an anti-business bias within academic anthropology has been widely noted (McCracken, 2013;Moeran & Garsten 2012, 9;Schwartzman, 1993, pp.…”
Section: Sympathy For the Less Wealthy And Powerfulmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review of journal articles, we observed that anthropology articles mentioned "colonialism" nearly 16 times as often as management journals and "racism" nearly 5 times as often. We are not surprised, given the selfconsciousness of the discipline about its ambivalent historical connection with colonial administrations (Baba, 2009;Comaroff, 2010;Low & Merry, 2010). Moreover, an anti-business bias within academic anthropology has been widely noted (McCracken, 2013;Moeran & Garsten 2012, 9;Schwartzman, 1993, pp.…”
Section: Sympathy For the Less Wealthy And Powerfulmentioning
confidence: 99%
“…For example, Nolan (2013a, p. 5), a senior anthropologist, wrote that much of what practicing anthropology has learned "has been studiously ignored by the academy." Even within the field of applied anthropology, Morais (2012, p. 276) claims that business anthropology is "marginalized" on account of its "engage[ment with] commerce" and apparent failure to help "to repair the world" as compared with most efforts at engagement (summarized by Low & Merry, 2010).…”
Section: What Can Anthropology Gain From Management?mentioning
confidence: 99%
“…He developed a framework for analysing adaptationmaladaptation and called engaged anthropologists to work with research participants in figuring out solutions to the problems of maladaptation (Low and Merry 2010). Engaged anthropology had its critics, particularly as during the cold war, the Central Intelligence Agency (CIA) and the US army in some cases hired anthropologist to advance geopolitical projects.…”
Section: Oscar Alfredo Forero Larrañagamentioning
confidence: 99%
“…Estas intervenciones provocan animados debates dentro de la disciplina (Baron 2010): si una parte de los investigadores escogen ir más allá de esta perspectiva y se implican en la creación del PCI, la mayoría observa este fenómeno a distancia. La cuestión del compromiso, en el centro mismo de la definición dada por la Unesco, es un reto fundamental en la reflexión de la antropología contemporánea sobre sí misma y una de las más recientes formulaciones de este debate que ha mostrado cómo las distintas aproximaciones de la disciplina desembocan en distintos tipos de compromiso, teórico o aplicado: desde la crítica cultural de la antropología académica a la investigación militante (Low & Merry 2010;Hale 2006).…”
Section: De La Etnología a Lo Inmaterial: El Papel De Los Etnólogosunclassified